Oxide-derived bismuth as an efficient catalyst for electrochemical reduction of flue gas - Yang, Fangqi (2023)
Post-combustion flue gas (mainly containing 5-40% CO2 balanced by N2 ) accounts for about 60% global CO2 emission. Rational conversion of flue gas into value-added chemicals is still a formidable challenge. Herein, this work reports a β-Bi2 O3 -derived bismuth (OD-Bi) catalyst with surface coordinated oxygen for efficient electroreduction of pure CO2 , N2, and flue gas. During pure CO2 electroreduction, the maximum Faradaic efficiency (FE) of formate reaches 98.0% and stays above 90% in a broad potential of 600 mV with a long-term stability of 50 h. Additionally, OD-Bi achieves an ammonia (NH3 ) FE of 18.53% and yield rate of 11.5 µg h-1 mgcat -1 in pure N2 atmosphere. Noticeably, in simulated flue gas (15% CO2 balanced by N2 with trace impurities), a maximum formate FE of 97.3% is delivered within a flow cell, meanwhile above 90% formate FEs are obtained in a wide potential range of 700 mV. In-situ Raman combined with theory calculations reveals that the surface coordinated oxygen species in OD-Bi can drastically activate CO2 and N2 molecules by selectively favors the adsorption of *OCHO and *NNH intermediates, respectively. This work provides a surface oxygen modulation strategy to develop efficient bismuth-based electrocatalysts for directly reducing commercially relevant flue gas into valuable chemicals.